Emenda constitucional nº 103/2019: análise da constitucionalidade da sistemática de cálculo da aposentadoria por incapacidade permanente em face do princípio da proibição do retrocesso social - MENDES, Maria Thereza de Sá (2024)
The social right to Social Security, as provided for in article 6 of the 1988 Federal Constitution, was modified by Constitutional Amendment nº 103/2019 in response to allegations of a financial deficit that could lead to budgetary unsustainability in a few years, given the condition in which was found. This work analyzes whether the changes made to retirement due to permanent disability, which significantly reduced its value in relation to the disability benefit and also created disparities between accidental and non-accidental retirement, violated the principle of replacing social regression since the Reform benefit due to permanent disability was reconfigured in a disproportionate and unreasonable way, without considering social reality or the search for social justice, foundations of the Democratic Rule of Law. Focus only on the alleged economic crisis and supposed actuarial criteria without justifiable support. The analysis used the deductive method and was based on bibliographical research, collecting data on legislation, doctrine and Brazilian jurisdiction. In the final financing, there was a violation of the constitutional principle of social regression, in that the reform affected the protective logic of the permanent disability benefit disproportionately, without providing a clear and well-founded justification for this.